Preferences for Facial and Vocal Masculinity in Homosexual Men: The Role of Relationship Status, Sexual Restrictiveness, and Self-Perceived Masculinity. (February 2013) - Valentová, Jaroslava; Roberts, S Craig; Havlíček, Jan
Studies on mate preferences usually examine heterosexual attraction; comparatively little is known about preferences of individuals whose sexuality is aimed at the same sex. We examined preferences of two groups of androphilic individuals—homosexual men and heterosexual women—for male facial and vocal level of masculinity. Facial images of 58 men and vocal recordings of 30 men were rated by 51 heterosexual women and 33 homosexual men for their attractiveness and masculinity-femininity. In both groups of raters, ratings of vocal attractiveness and masculinity were positively correlated, but there was no overall preference for facial masculinity. After splitting raters according to their relationship status, sexual restrictiveness, and self-rated masculinity, we found significant preferences for masculine voices only in single homosexual men and coupled heterosexual women, while a preference for feminine male faces was found in coupled homosexual men. Furthermore, homosexual men describing themselves as relatively masculine significantly preferred masculine voices but also more feminine male faces. Our results demonstrate that conditional mate preferences are not restricted to heterosexual interactions, and homosexual men prefer a mixture of masculine and feminine traits in their potential male partners.